You are on page 1of 39

Chain Rule

If y = f(u) is a differential function of u and u in turn is


a differentiable function of x, that is u = g(x), then
y = f (g(x)) is a differentiable function of x and its
derivative is given by the product
dy dy du
=
dx du dx

The chain rule states that the change in y w.r.t. x is


the product of two rates of change.

1
Solution
4
x
• Differentiate g(x) =
1 − 3x
• Write g(x) =  x 
1
4
1
where u = x is the inner
  = u4
 1 − 3x  1 − 3x

function and u1 / 4 is the outer function. Then


−3
1 4 '
g ( x) = u u ( x)
'

4
−3
1 x  4  (1 − 3 x)(1) − x(−3) 
g ( x) = 
'
  
4  1 − 3x   (1 − 3 x ) 2

−3
1 x   1  4 1
=     = 2
4  1 − 3 x   (1 − 3 x ) 2  3 5
4 x (1 − 3 x ) 4
4
Differentiation using Chain Rule

• y = f(u) and u = g(x)

d n n −1 du d u u du d 1 du
u = nu e =e ln u =
dx dx dx dx dx u dx

d du d du
sin u = cos u cos u = − sin u
dx dx dx dx

d du d du
tan u = sec 2 u cot u = − csc u
2

dx dx dx dx

d du d du
sec u = sec u tan u csc u = − csc u cot u
dx dx dx dx 3
Example

• Write the composite function in the form of f(g(x)) and then find the derivative
using the chain rule.

• (i) y = (1 − x 2 )10

• (ii)
y = sin x

• (iii) y = tan(sin x)

• (iv) y = sin( x cos x)

4
Solution (i)

• (i) y = f ( g ( x)) = f (u ) = (1 − x 2 )10



• Let u = g(x) = 1 - x2 and y = f(u) = u10
Then,
dy dy du
=
dx du dx
( )
= 10u 9 (−2 x)

= −20 x(1 − x 2 )9

5
Solution (ii)

• (ii) y = f ( g ( x)) = f (u ) = sin x


• Let u = g(x) = sin x and y = f(u) = u

dy dy du 1 −1/ 2
= = u cos x
dx du dx 2
cos x
=
2 u
cos x
=
2 sin x

6
Solution (iv)

• (iv) y = sin( x cos x)

• Let u = x cos x and y = f(u) = sin u

dy dy du
= = cos u[ x(− sin x) + cos x.1]
dx du dx
= cos( x cos x)(cos x − x sin x)

7
Example- level of C 02

• An environmental study of a certain community suggests that the average daily level
of carbon monoxide in the air may be modeled by the formula

C ( p ) = 0.5 p 2 + 17

parts per million when the population is p thousand.


It is estimated that t years from now,
2
the population of the community will be

2
p(t) = 3.1 + 0.1 t
thousand. At what rate the carbon monoxide level be changing with respect to time 3
years from now.

8
Solution

dC dC dp  1 
( )
−1
= =  0.5 p 2 + 17 2 (0.5)(2 p )[ 0.2t ]
dt dp dt  2 
When t = 3, p(3) = 3.1 + 0.1(3)
2
=4

dC 1 −1

t =3 =  (0.5.4 + 17) (4)[ 0.2(3)] = 0.24
2 2
dt 2 

The carbon monoxide level will be changing at the rate of 0.24 parts per million.
It will be increasing because the sign of dC is positive.

dt

9
Example: Tumor Growth

• A tumor grows such that its radius expands at a constant rate k. Determine the rate
of growth of the volume of the tumor when the radius is one centimeter. Assume the
shape of the tumor is well approximated by a sphere.
• (Volume of sphere, V = 4 πr 3 )
3
• Solution 4 3
• Volume of a sphere with radius r is
V = πr
3
• r and V change with time, and given dr
=k
dt
• So,
dV dV dr 4
= = π 3r 2 k = 4πr 2 k
dt dr dt 3
• When r = 1 cm,

dV
= 4πr 2 k = 4πk
dt 10
Example: spider web

• A spider moves horizontally across the ground at a constant rate k, pulling a thin
thread with it. One end of the thread is pinned to a vertical wall at height h above the
ground and does not move. The other end moves with the spider. Determine the rate
of the elongation of the thread.

• Solution

h l

x
h = height of pinned point
x = position of spider
l = length of thread

11
Spiderweb solution

• From diagram of Pythagoras,

l = x +h
2 2 2

dx
• We know h is constant and rate of spider moves with time is =k
dt
Need to find rate of elongation of thread w.r.t. t i.e dl

=?
dt
dl dx
2l = 2 x + 0
• So, dt dt
dl x dx x xk
= =
l
k=
dt l dt x2 + h2
12
Implicit Differentiation

• The equation y = 1 − x 2 explicitly defines f(x) = 1 − x 2


as a function of x for − 1 ≤ x ≤ 1

The same function can also be defined implicitly by the equation


x 2 + y 2 = 1 as long as we restrict y by 0 ≤ y ≤ 1
To find the derivative of the explicit form, we use the chain rule;
1 −1
d d 1 −x
1 − x 2 = (1 − x 2 ) 2 = (1 − x 2 ) 2 (−2 x) =
dx dx 2 1 −x2
The derivative of the implicit function is

d 2 d
(x + y 2 ) = (1)
dx dx
13
Implicit Differentiation

• So, dy
2x + 2 y =0
dx
dy − x x
= =−
dx y 1− x2

The procedure illustrated above is called implicit differentiation

Consider another example;

x 2 y 3 − 6 = 5 y 3+ x
d 3 3 d d d 3 d
x 2
(y ) + y ( x ) − (6 ) = 5 ( y ) + ( x )
2

dx dx dx dx dx
 2 dy   2 dy 
x 3y  + y ( 2 x) − 0 = 5 3 y  +1
2 3

 dx   dx  14
Continue…

dy
3 y − 15 y )
2 2 2
= 1 − 2 xy 3
dx
dy 1 − 2 xy 3
= 2 2
dx 3x y − 15 y 2

• The derivative involves both x and y and that is acceptable

15
Example

• Find y' if

Solution

16
Example

• Prove that an equation of the tangent line to the graph of the hyperbola

at the point P ( x0 , y0 ) is

Solution

So the equation of the tangent line at the point P(x0,y0) is

17
Continue…

• So the equation of the tangent line at the point P ( x0 , y0 ) is

Point P is on hyperbola so,

And equation of tangent line is

18
• Find all points (x, y) on the graph ofx2/3 + y2/3 = 8
• (see diagram.) where lines tangent to the graph at (x, y) have slope -1 .

19
Solution

x 2/3
+y 2/3
=8
2 −1/ 3 2 −1/ 3 dy
x + y =0
3 3 dx

dy − x −1/ 3
= −1/ 3
dx y

dy − x −1/ 3 − y1/ 3
= −1/ 3 = 1/ 3 = −1
dx y x

20
Continue…

dy − y1/ 3
• Solve the equation = 1/ 3 = −1 and get the points on the
dx x
• curve where the tangent passing through those points have slope -1

• Points: (8,8) and (-8,-8)

21
DERIVATIVE FORMULAS FOR THE INVERSE
TRIGONOMETRIC FUNCTIONS

• If u is differentiable function of x, then


d 1 du d − 1 du
(sin −1 u ) = −1
(cot u ) =
dx 1 − u 2 dx dx 1 + u 2 dx

d − 1 du d
(sec −1 u ) =
1 du
(cos −1 u ) = dx
dx 1 − u 2 dx | u | u 2 − 1 dx

d 1 du d −1 −1 du
−1
(tan u ) = csc u ) =
dx 1 + u 2 dx dx | u | u 2 − 1 dx

22
Proof of d 1 du
(sin −1 u ) =
dx 1 − u 2 dx

• We shall prove the first formula and leave the others as problems.

• α = sin −1 f ( x) ,
Let u = f(x)
sin α = f ( x)
d d
(sin α ) = ( x)
dx dx

cos α =1
dx
dα 1 1 1
= = = (cos 2 α + sin 2 α = 1)
dx cos α 1 − sin α
2
1 − [ f ( x)]2

d d du 1 du
(sin −1 u ) = (sin −1 u ) =
dx du dx 1 − u 2 dx 23
Example

• Find the derivative of the following functions:

• 1. y = sin −1 (2 x + 1)
−1
• 2. y = tan x2 + 1

• 3. y = csc −1 (2 x 2 )

24
Solution

• 1. y = sin −1 (2 x + 1) , Let u = (2x + 1)


dy d −1 du 1 2
= (sin u ) = ( 2) =
dx du dx 1 − (2 x + 1) 2
− 4x 2 − 4x

• 2. y = tan −1 x 2 + 1 , u = x2 +1

1
dy d du 1 1 2 − 1 x
= (tan −1 u ) = ( x + 1) 2
( 2 x ) =
dx du dx 1 + ( x 2 + 1) 2 1 + ( x 2 + 1) x2 +1

x
• Try 3… =
( x 2 + 2) x 2 + 1

25
Differentiating Logarithmic Functions with Bases other than e

• If u = f(x) is a function of x, and y = log b u is a logarithm with


base b, d 1 1 du
(log b u ) = .
dx ln b u dx
ln u
Proof: Change log b u to base e and take ln on both sides of y= and
differentiate ln b

Example
Find the derivative of y = 3 log 7 ( x 2 + 1)

Solution
3 dy dy du
u = x +1 2
y= ln u =
ln 7 dx du dx
1 3 6 x
u' = 2x = 2 x =
ln 7 x 2 + 1 ln 7 x 2 + 1
26
Example

• Find the derivative of 3 ln xy + sin y = x2


• Solution
This is an implicit function.

27
Another example

y = ( sin x )
x
• Find the derivative of

• Solution

28
Other Formulas for Derivatives of Exponential Functions

u
• If u is a function of x, we can obtain the derivative of e
an expression in the form :

If we have an exponential function with some base b, we have the following derivative

y = bu
ln y = u ln b 1 dy du
⇒ = ln b
y dx dx
29
Example

x2
• Find the derivative of y = 10
• Solution

b = 10 and u = x2

ln y = x 2 ln 10
1 dy
= 2 x ln 10
y dx
dy x2
= 10 2 x ln 10
dx 30
Example

• Show that satisfies the equation

Solution

31
Example

• So

32
Logarithmic differentiation

• Find the derivative of e 2 x (2 x − 1) 6


y= 3
( x + 5) 2 (4 − 7 x)
• Solution

 e 2 x (2 x − 1) 6 
ln y = ln  3 
 ( x + 5) 2
( 4 − 7 x ) 
= 2 x ln e + 6 ln(2 x − 1) − 2 ln( x 3 + 5) − ln(4 − 7 x)
1 dy  1   1   1 
= 2 + 6 (2) − 2  3 (3x 2 ) −  (−7)
y dx  2x − 1  x +5  4 − 7x 

• Complete the steps…


• Remember ln e = 1

33
Related rates and Applications

• Example 1
• A spherical balloon is being filled with a gas in such a way that when the
radius is 2ft, the radius is increasing at the rate of 1/6ft./min. How fast is
the volume changing at this time?
• (Volume of sphere is V = 4 πr 3 )
3
dV
• Solution Need to find dt at the
4 3 dr 1
• V = πr time when r= 2 and =
3 dt 6
dV d 4 3
= ( πr )
dt dt 3 dV 1
r =2 = 4π (2) 2  
dr
dt 6
= 4πr2

dt =
3 34
Example 2

A person 6ft. tall walks away from a streetlight at the rate of 5 ft/s.
If the light is 18ft above ground level, how fast is the person’s
shadow lengthening

Solution
Let x = length of the shadow
y = distance of the person from the streetlight

dy dx
= 5 ft / s =?
dt dt 18

Because of similar triangles, 6

x x+ y y x
=
6 18
35
Continue…

x x+ y
=
6 18
y = 2x
dy dx
=2
dt dt
dx
5=2
dt
dx
dt
= 2 .5 → The shadow is lengthening at the rate of 2.5ft/s.

36
Example 3

• Consider a piece of ice melting in the shape of a sphere that is melting at a


3 4
rate of 5in / min ( Volume of sphere is V = πr 3 )
3

• (a) Model the volume of ice by a function of the radius r

• (b) how fast is the radius changing at the instant when the radius is 4 inch

• (c) how fast is the surface area changing at the same instant
• (surface area of sphere is S = 4πr 2 )

• (d) what assumption are you making in this model about the shape of the
ice.

37
Solution of melting ice

• Given dV and r = 4
= −5
dt

• (a) Model of ice takes the shape of sphere, so


4 3
V = πr
3
• (b) dV dr
= 4πr 2
dt dt
dr
− 5 = 4π (4) 2
dt
dr − 5
• = ~ −0.025 → the radius is decreasing at the rate of
dt 64π 0.025in/min

38
Continue…

• (c)
S = 4πr 2

dS dr
= 8πr
dt dt
• With r = 4 and
dr − 5
= ~ −0.025
dt 64π
dS  −5 
= 8π (4)  = −2.5in / min
2

dt  64π 
surface area is decreasing at the rate of − 2.5in / min
2

(d) Assumption: Ice is in the shape of a sphere

39